Ldlr−/− and ApoE−/− mice better mimic the human metabolite signature of increased carotid intima media thickness compared to other animal models of cardiovascular disease. (September 2018) - Saulnier-Blache, Jean Sébastien; Wilson, Rory; Klavins, Kristaps; Graham, Delyth; Alesutan, Ioana; Kastenmüller, Gabi; Wang-Sattler, Rui; Adamski, Jerzy; Roden, Michael; Rathmann, Wolfgang; Seissler, Jochen; Meisinger, Christine; et al.
Abstract: Background and aims: Preclinical experiments on animal models are essential to understand the mechanisms of cardiovascular disease (CVD). Metabolomics allows access to the metabolic perturbations associated with CVD in heart and vessels. Here we assessed which potential animal CVD model most closely mimics the serum metabolite signature of increased carotid intima-media thickness (cIMT) in humans, a clinical parameter widely accepted as a surrogate of CVD. Methods: A targeted mass spectrometry assay was used to quantify and compare a series of blood metabolites between 1362 individuals (KORA F4 cohort) and 5 animal CVD models: ApoE − / −, Ldlr − / −, and klotho-hypomorphic mice ( kl/kl ) and SHRSP rats with or without salt feeding. The metabolite signatures were obtained using linear regressions adjusted for various co-variates. Results: In human, increased cIMT [quartile Q4 vs. Q1] was associated with 26 metabolites (9 acylcarnitines, 2 lysophosphatidylcholines, 9 phosphatidylcholines and 6 sphingomyelins). Acylcarnitines correlated preferentially with serum glucose and creatinine. Phospholipids correlated preferentially with cholesterol (total and LDL). The human signature correlated positively and significantly with Ldlr − / − and ApoE − / − mice, while correlation with kl/kl mice and SHRP rats was either negative and non-significant. Human and Ldlr − / − mice shared 11 significant metabolites displaying the same direction of regulation: 5 phosphatidylcholines, 1 lysophosphatidylcholines, 5 sphingomyelins; ApoE − / − mice shared 10. Conclusions: The human cIMT signature was partially mimicked by Ldlr − / − and ApoE − / − mice. These animal models might help better understand the biochemical and molecular mechanisms involved in the vessel metabolic perturbations associated with, and contributing to metabolic disorders in CVD. Highlights: Metabolomics allows access to the metabolic perturbations associated with cardiovascular disease (CVD). Increased carotid intima-media thickness (cIMT) is a surrogate of CVD. Human blood metabolite signature of increased cIMT is made of acylcarnitines and phospholipids. LDLR−/− and ApoE−/− mice mimicked the phospholipid part of cIMT signature.